PENGARUH VALUE ADDED TERHADAP NILAI PERUSAHAAN NON KEUANGAN - Cahyadi, Olivina; Anggraeni, Fanny (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this research is to obtain empirical evidence regarding several factors that can affect the value of non-financial companies listed on the Indonesia Stock Exchange (IDX). Some of the factors referred to are Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), company size, company age, capital structure, financial performance, and net profit margin. The population includes all non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. Purposive sampling was used as a technique for selecting the sample. There are 150 non-financial companies that meet the criteria and as many as 750 sample data used in this study. Sample data was tested using multiple regression methods. The results of the research conducted show that Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), structural capital value added (STVA), company size, company age, and capital structure have no effect on firm value, while financial performance and net profit margin affect the value of the company.